Uncovered set choice rule - Michele Lombardi (Queen Mary University of London, Department of Economics, 2006)
I study necessary and sufficient conditions for a choice function to be rationalised in the following sense: there exists a complete asymmetric relation T (a tournament) such that for each feasible (finite) choice situation, the choice coincides with the uncovered set of T. This notion of rationality explains not only cyclical and context dependent choices observed in practice, but also provides testable restrictions on observable choice behavior.
Keywords: D01; 330; Rationalizability; Uncovered set; Intransitive choice; Soziale Wohlfahrtsfunktion; Abstimmungsregel; Theorie